ANALISIS EKSTERNAL DALAM UPAYA PENGEMBANGAN MUTU PELAYANAN RAWAT INAP DI RSUD PANEMBAHAN SENOPATI BANTUL - Fitra Sari; Susanto Susanto (JMMR (Jurnal Medicoeticolegal dan Manajemen Rumah Sakit), 2015)
Background: Panembahan Senopati Hospital in Bantul as one government hospital in order to survive and be able to compete with other centers must be able to develop it self according with quality demand. Effort to the win that competition can be done by improving service quality and providing services properly as expected by the customerThere for, Panembahan Senopati hospital need to have a quality plan by identifying their customer need to improve the quality services. Based on customer needidentification process, service quality development stretegies can be arranged. Objectives: To know the gap between expectation and reality external customer for the quality of care in Panembahan Senopati Bantul Hospital, knowing the gap between expectation and reality of customer as an ingredient in developing a strategy of development of quality service in Panembahan Senopati Hospital. Methods: The research is quantitative research with cross sectional design. The study was conducted on November 2013 in Panembahan Senopati Bantul Hospital. The sampel Obtained was 100 people. The sampling design is random sampling. The data analysis with defferent test average in pairs (t-test). Result: The result showed that there are significant gaps between the average expectation and reality (p<0,05). The significant gap score on Class II there are dimension Emphaty of nurse with gap=0,010. Class III and VVIP there is gap significant in communication dimension with gap=0,049 andgap 0,011 and assurance dimension with gap= 0,001 on Class III. The significant gap score on Classn1there are dimension tangible with gap 0,016. While the other dimension are not gap significant. Conclusion: Quality of service in Panembahan Senopati Hospital for VVIP still does not meet customer expectations, then quality of service in Panembahan Senopati Hospital for class II and III still does meet customer expectation.